60 Treatment Of Achillodynia With Local Injections Of Autologous Conditioned Serum (acs). (5th September 2014) - Majewski, Martin; von Wehren, Lutz; Blanke, Fabian
Abstract : Introduction: While a common problem, achillodynia remains difficult to treat, often chronifying. Excentric exercise is a generally accepted treatment option. Rat experiments have shown in the past that local ACS injection has potential in tendon repair creating a local environment that favours organised tissue repair [Majewski, Heisterbach]. ACS contains anti-inflammatory cytokines and potentially regenerative growth factors [Wehling]. It has shown clinical efficacy in joint and radiculopathy treatment. Here we report the treatment of regular out patients. Methods: Inclusion: 25 achillodynia patients with MRI-confirmed structural changes, tendinous effusion, and thickening, pain upon palpation, at rest and in exercise, persisting during 6 weeks of PT plus reduction of sports activity with no prior injuries or surgery. Treatment: 3 injections of 5 mL in 7 day intervalls. First injection into punctum dolens. 2 subsequent injection peritendinous. Full weight bearing, no sports for 4 weeks post last injection. Excentric exercise started at 4 weeks after injections. No NSAID for 6 months. Documentation: MRI at 0 and 6 months past end of injections. VISA-A (NRS-11) at T = 0 and T = 6 months [Figure 1 ]. Results: Of 25 patients (11 female), mean age 50.4 ± 13.7 years with mean duration of symptoms 6.7 ± 0.56 months 100% reported an improvement in pain. 88% reported regained sports activity, 100% experienced structural improvement in MRI at 6 months. Injection into punctum dolens causes discomfort, peritendinous injections are well tolerated. Discussion: ACS has the potential to improve tendon- but also muscle regeneration [Wright-Carpenter]. It is retrieved from autologous patient's blood which is incubated for 6–9 hrs in patented devices and accumulates both anti-inflammatory cytokines and growth factors [Table 2 ]. It is proposed that through synergistic action of signalling proteins tendon tissue is enabled to regenerate more effectively. References: Majewski, et al . Am J Sports Med. 2009;37(11):2117–2125 Heisterbach et al . KSSTA. 2012;20:1903–1910 Wehling, et al . Biodrugs 2007;21(5):323–33 Wright-Carpenter, et al . Int J Sports Med. 2007;25(8):582–587 Wright-Carpenter, et al . Int J Sports Med. 2007;25(8):588–59